(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The article represents the research work based on the analysis of the main approaches to a concept and to creation of the "knowledge management" model in organizations. The authors have carried out organizational diagnostics of SPAO "RESO-Garantiya", revealed its weaknesses and prepared recommendations how to increase competitiveness by means of reorganization of a personnel management system.